Topical effects of 16, 16 dimethyl prostaglandin E2 on gastric acid secretion and mucosal permeability to hydrogen ions in dogs. Issue 9 (September 1978) - Cheung, L Y; Lowry, S F; Perry, J; Larson, K
Abstract : The effects of luminal instillation of 16, 16 dimethyl PGE2 (dmPGE2) on gastric acid secretion and back diffusion of H+ were studied in anaesthetised dogs which were prepared with a segment of the greater curvature of the stomach mounted in a double lumen chamber. This model permitted simultaneous evaluation of two segments of mucosa, one control and the other test, supplied by the same vascular pedicle. Imfusion of histamine (1.0 microgram/kg/min, intravenously) stimulated brisk acid secretion in both chambers. Topical application of 25 microgram dmPGE2 in 20 ml 0.3 M HC1 to the test chamber for 30 minutes prevented acid secretion from the test mucosa during a second histamine infusion. Since the control chamber showed no evidence of inhibition this indicates that dmPGE2 acted directly on the secretory cells, rather than after absorption from the bloodstream. This observation, however, does not exclude a possible local effect on mucosal blood flow. Direct exposure of the gastric mucosa to dmPGE2 increased the rate of back diffusion of H+ because of disruption of the permeability barrier, indicated by increased H+ back diffusion, Na+ efflux, and a reduction in potential difference. However, H+ loss was small compared to the reduction in acid output.